United territorial communities in Ukraine in the context of fiscal decentralization - Alina Korbutiak; Zhanna Lysenko; Nataliya Sokrovolska; Artur Oleksyn; Eduard Yurii (Problems and Perspectives in Management, 2019)
Since the beginning of the administrative and territorial reform in Ukraine, the financial decentralization process has been intensified. It aims at optimizing the budgetary resource redistribution in order to make communities financially independent. This significantly increases the financial capacity for self-organization and self-development of a united territorial community, which determines the need to apply valuation methods to increase the territory’s investment attractiveness.The article outlines the peculiarities of the united territorial communities (UTCs) management under fiscal decentralization, taking into account the need to apply current methods of value-oriented management. At the same time, the use of SWOT analysis as one of the methods of value-oriented management made it possible to evaluate the efficiency and attractiveness of UTCs under decentralization. The financial activity of 665 UTCs was analyzed and the model for managing the united territorial community was created. It is emphasized that the modern understanding of financial support for united territorial communities remains unresolved today, and the expediency to introduce changes in the UTC, which envisage using the subsidiarity principles, is not justified.The key directions for managing the UTCs are identified. This refers to communities that began their activities and already faced the first challenges: management of available resources, provision of needs and sustainable development of the community, changes in the ratio of their income and expenditure components, increase in the budget income per capita.It is recommended to focus on tools of value-oriented management in the united territorial communities in order to attract investors and increase the financial capacity of local authorities.